BIX-01294-enhanced chemosensitivity in nasopharyngeal carcinoma depends on autophagy-induced pyroptosis. (21st October 2020) - Li, Qian; Wang, Min; Zhang, Yan; Wang, Liuqian; Yu, Wei; Bao, Xiaomin; Zhang, Biyun; Xiang, Yanghong; Deng, Anchun
Abstract: Nasopharyngeal carcinoma (NPC) is a common cancer in southern China and Southeast Asia. Nowadays, radiotherapy is the therapy of choice for NPC patients, and chemotherapy has been found as an alternative treatment for advanced NPC patients. However, finding novel drugs and pharmacologically therapeutic targets for NPC patients is still urgent and beneficial. Our study showed that BIX-01294 (BIX) can induce autophagic vacuoles formation and conversion of LC3B-I to LC3B-II in NPC cells in both dose- and time-dependent manners. Notably, the combination of BIX and chemotherapeutic drugs significantly decreased the cell viability and increased the lactate dehydrogenase release. Meanwhile, BIX plus cis -platinum (Cis) treatment induced pyroptosis in NPC cells as featured by cell swelling and bubble blowing from the plasma membrane, the increased frequency of annexin V and propidium iodide (PI) double-positive cells, as well as the cleavage of gasdermin E (GSDME) and caspase-3. Moreover, the deficiency of GSDME completely shifted pyroptosis to apoptosis. Furthermore, the inhibition of autophagy by chloroquine and the knockout of ATG5 gene significantly blocked the BIX-induced autophagy as well as pyroptosis in both in vitro and in vivo studies. Our data demonstrated that BIX-combined chemotherapeutic drugs could induce the Bax/caspase-3/GSDME-mediated pyroptosis through the activation of autophagy to enhance the chemosensitivity in NPC.